Streamlined Quantification of Microglial Morphology in Mouse Brains Using 3D Immunofluorescence Analysis - de Donato, Maria Helena; Kouchaeknejad, Armin; de Donato, Andreu; Van Der Walt, Gunter; Puighermanal, Emma (Bio-protocol, 2025)
Microglial cells are crucial patrolling immune cells in the brain and pivotal contributors to neuroinflammation during pathogenic or degenerative stress. Microglia exhibit a heterogeneous "dendrite-like" dense morphology that is subject to change depending on inflammatory status. Understanding the association between microglial morphology, reactivity, and neuropathology is key to informing treatment design in diverse neurodegenerative conditions from inherited encephalopathies to traumatic brain injuries. However, existing protocols for microglial morphology analyses lack standardization and are too complex and time-consuming for widescale adoption. Here, we describe a customized pipeline to quantitatively assess intricate microglial architecture in three dimensions under various conditions. This user-friendly workflow, comprising standard immunofluorescence staining, built-in functions of standard microscopy image analysis software, and custom Python scripts for data analysis, allows the measurement of important morphological parameters such as soma and dendrite volumes and branching levels for users of all skill levels. Overall, this protocol aims to simplify the quantification of the continuum of microglial pathogenic morphologies in biological and pharmacological studies, toward standardization of microglial morphometrics and improved inter-study comparability. Key features • Comparison of 3D microglial architecture between physiological and pathological conditions. • Quantitative assessment of critical microglial morphological features, including soma volume, dendrite volume, branch level, and filament length. • Simplified, semi-automated data export and analysis through simple Python scripts. Graphical overview.